Jeroen de Rijke & Willem de Rooij : Spaces and films 1998-2002. - Van Abbemuseum Eindhoven; Villa Arson, Nice; Debbaut, Jan; Diederichsen, Diedrich; Gateau, Laurence; Meyer-Hermann, Eva; Schöllhammer, Georg (Eindhoven Nice : Van Abbemuseum Villa Arson, 2003)
Since 1994 the Dutch artists Jeroen de Rijke & Willem de Rooij have been collaborating on a comprehensive oeuvre of films. This artist's book focuses on their last four 35 mm films (1998-2002), paying particular attention to the growing importance of the phenomenological and iconographic aspects of their work. In addition it illustrates specific exhibition situations in a visual manifesto of their artistic thinking, complemented by enlightening essays by Diedrich Diederichsen and Georg Schöllhammer and detailed descriptions of the four films.
ind. tent., gr. tent., geselecteerde bibliog. p. 96-99
Engels
Frans
Exhibition. Jeroen de Rijke & Willem de Rooij : Spaces and films / Espaces et films 1998-2002 Van Abbemuseum Eindhoven (2000-05-27. 2000-09-03). Villa Arson Nice. (2002-06-16. 2002-04-20)
boek
Keywords: de Rijke, Jeroen; de Rooij, Willem